Treatment of industrial wastewater using kariba weed (salvinia molesta SP.) - Siti Hafieza Idayu, Che Saidi (2019)
Nowadays, with the industrial and modern technologies develop rapidly, water pollution has become one of the massive problems for not only third world countries and development countries but also to very advanced countries. Phytoremediation process is environmental friendly and low cost treatment method. This research was conducted to explore the feasibility and efficiency of aquatic plants remediate effluent from industrial wastewater that has been treated. The objectives of the research were to characterize the status of industrial wastewater in Gebeng industrial estate and determine the phytoremediation efficiency of Salvinia Molesta sp. in removing pollutant from wastewater. To achieve these objectives, Kariba weed was selected for the research. The water parameters that had been monitored and tested were dissolved oxygen (DO), pH, turbidity, total suspended solids (TSS), chemical oxygen demand (COD), biochemical oxygen demand (BOD), ammoniacal nitrogen (NH3-N), copper (Cu), cadmium (Cd), and lead (Pb). From the overall results obtained in the experiments, 50% concentration of wastewater contributed the highest percentage removal efficiency were 8.16%, 11.69% and 12.79% of pH, 17.95%, 33.70% and 41.88% of BOD, 26.09%, 39.13% and 60.87% of NH3-N, 26.67%, 43.33% and 56.67% of COD, 28.57%, 50% and 64.29% of Pb, 33.33%, 50% and 66.67% of Cd, 21.05%, 31.58% and 47.37% of Cu for week 1, week 2 and week 3 while percentage of DO is increased which were 5.27%, 15.96% and 19.73% for week 1 to week 3. Furthermore, the increasing of total suspended solid for 50% concentration of wastewater was lowest among three concentration which were 5.26%, 21.05% and 38.60% for week 1 to week 3. But for the turbidity, 75% concentration of wastewater contributed the highest percentage of increasing efficiency which were 5.62%, 12.29% and 15.05% for week 1, week 2 and week 3. Comparisons done by three different concentration and 50% concentration of wastewater was the most suitable to remove most of the parameters.